Overall survival of myelodysplastic syndrome patients after azacitidine discontinuation and applicability of the North American MDS Consortium scoring system in clinical practice. Issue 12 (19th March 2021) - Clavio, Marino; Crisà, Elena; Miglino, Maurizio; Guolo, Fabio; Ceccarelli, Manuela; Salvi, Flavia; Allione, Bernardino; Ferrero, Dario; Balleari, Enrico; Finelli, Carlo; Poloni, Antonella; Selleri, Carmine; et al.
Abstract : Background: Azacitidine (AZA) is the standard treatment for myelodysplastic syndromes (MDS); however, many patients prematurely stop therapy and have a dismal outcome. Methods: The authors analyzed outcomes after AZA treatment for 402 MDS patients consecutively enrolled in the Italian MDS Registry of the Fondazione Italiana Sindromi Mielodisplastiche, and they evaluated the North American MDS Consortium scoring system in a clinical practice setting. Results: At treatment discontinuation, 20.3% of the patients were still responding to AZA, 35.4% of the cases had primary resistance, and 44.3% developed adaptive resistance. Overall survival (OS) was better for patients who discontinued treatment while in response because of planned allogeneic hematopoietic stem cell transplantation (HSCT; median OS, not reached) in comparison with patients with primary resistance (median OS, 4 months) or adaptive resistance (median OS, 5 months) or patients responsive but noncompliant/intolerant to AZA (median OS, 4 months; P = .004). After AZA discontinuation, 309 patients (77%) received best supportive care (BSC), 60 (15%) received active treatments, and 33 (8%) received HSCT. HSCT was associated with a significant survival advantage, regardless of the response to AZA. The North American MDS Consortium scoring system was evaluable in 278 of the 402 cases: patients at high risk had worse OS than patients at low risk (3 and 7 months, respectively; P < .001). The score was predictive of survival both in patients receiving BSC (median OS, 2 months for high‐risk patients vs 5 months for low‐risk patients) and in patients being actively treated (median OS, 8 months for high‐risk patients vs 16 months for low‐risk patients; P < .001), including transplant patients. Conclusions: Real‐life data confirm that this prognostic scoring system for MDS patients failing a hypomethylating agent seems to be a useful tool for optimal prognostic stratification and for choosing a second‐line treatment after AZA discontinuation. Abstract : Overall survival after azacitidine discontinuation is better for patients who have discontinued treatment while in response because of planned allogeneic hematopoietic stem cell transplantation in comparison with patients who have primary or adaptive resistance or patients who are responsive but noncompliant/intolerant to azacitidine. The North American MDS Consortium scoring system for myelodysplastic syndrome patients failing a hypomethylating agent is easily applicable and predicts survival after azacitidine discontinuation in a real‐life setting.